2021
DOI: 10.1021/acs.est.1c03754
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Short-Term Exposure to Fine Particulate Matter with Neural Damage Biomarkers: A Panel Study of Healthy Retired Adults

Abstract: Exposure to fine particulate matter (PM 2.5 ) is associated with various adverse health effects, such as respiratory and cardiovascular diseases. This study aimed to evaluate the association of PM 2.5 with neural damage biomarkers. A total of 34 healthy retirees were recruited from Xinxiang Medical University from December 2018 to April 2019. Concentrations of PM 2.5 constituents including 24 metals and nonmetallic elements and 6 ions, and 5 biomarkers of neural damage including brainderived neurotrophic facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 87 publications
2
4
0
Order By: Relevance
“…A comprehensive review revealed that elevated levels of PM exposure, even for short durations (ie, a few hours to days), can result in unstable brain haemodynamics 42. A study suggested that short-term PM exposure damaged neurons, thus negatively affecting the central nervous system 43. Another study noted positive associations between monthly short-term exposure to fine PM and ArI44; this result corroborated the current results.…”
Section: Discussionsupporting
confidence: 85%
“…A comprehensive review revealed that elevated levels of PM exposure, even for short durations (ie, a few hours to days), can result in unstable brain haemodynamics 42. A study suggested that short-term PM exposure damaged neurons, thus negatively affecting the central nervous system 43. Another study noted positive associations between monthly short-term exposure to fine PM and ArI44; this result corroborated the current results.…”
Section: Discussionsupporting
confidence: 85%
“…This allows the C‐R function to be applied directly on the time‐resolved exposure concentration profile. This assumption of micro‐physiological response is consistent with research linking elevated levels of biomarkers for example lung inflammation, cardiovascular effects, DNA damage and decreased lung function with increased pollution levels 15‐19 …”
Section: Development Of the New Metricsupporting
confidence: 81%
“…This assumption of micro-physiological response is consistent with research linking elevated levels of biomarkers for example lung inflammation, cardiovascular effects, DNA damage and decreased lung function with increased pollution levels. [15][16][17][18][19] On the basis of these insights, the assumptions behind the Logue…”
Section: Theoretical Casementioning
confidence: 99%
“…In a panel study, Tang et al examined the air pollutant (including PM) exposure in Chinese people aged 60–69 years, showing that air pollution exposure could induce alterations of neurodegenerative biomarkers, such as Aβ 40 , Aβ 42 , α-synuclein, PrPC, Tau (pThr181), and the activation of microglia represented by the over-expression of S100B and microglial triggering receptor expressed on myeloid cells2 (TREM2) [ 71 ]. Our recent findings from a panel study on healthy retired adults demonstrated that PM 2.5 concentration increments were associated with increases in the biomarkers of neural damage, including a neurofilament light chain (NfL), neuron-specific enolase, and the activation of microglia (S100B) in serum [ 72 ]. Meanwhile, several constituents of ambient PM 2.5 , such as Cu, Zn, Ni, Mn, Sn, V, Rb, Pb, Al, Be, Cs, Co, Th, U, Cl − , and F − were found to be significantly associated with serum levels of NfL [ 72 ].…”
Section: Evidence From Epidemiological Investigationsmentioning
confidence: 99%
“…Our recent findings from a panel study on healthy retired adults demonstrated that PM 2.5 concentration increments were associated with increases in the biomarkers of neural damage, including a neurofilament light chain (NfL), neuron-specific enolase, and the activation of microglia (S100B) in serum [ 72 ]. Meanwhile, several constituents of ambient PM 2.5 , such as Cu, Zn, Ni, Mn, Sn, V, Rb, Pb, Al, Be, Cs, Co, Th, U, Cl − , and F − were found to be significantly associated with serum levels of NfL [ 72 ].…”
Section: Evidence From Epidemiological Investigationsmentioning
confidence: 99%